The role of primary and secondary air on wood combustion in cookstoves - Thomas Kirch; Cristian H. Birzer; Paul R. Medwell; Liam Holden (International Journal of Sustainable Energy, 2018)
A two-stage solid fuel research furnace was used to examine the claim that through forced draught greater mixing and more complete combustion could be achieved. By varying the primary air (PA) and secondary air (SA) flow the influence on the combustion process was investigated. In the first part of the combustion, when the release of volatile compounds predominates, the variation of neither PA nor SA had a significant influence. In the second part when mainly char is oxidised an increase in both PA and SA lead to a rising nominal combustion efficiency (${\rm NCE} = {\rm CO}_{2}/({\rm CO}_{2}+{\rm CO}$)), with a greater impact observed with SA. Furthermore higher air flows caused the heat transfer, to a pot above the furnace, to decline. Therefore forced draught does lead to greater mixing and mitigation of emissions, but in the presented configuration a trade-off between a higher NCE and a lower heat transfer needs consideration.